(untitled) (Journal of Enam Medical College, 2012)
Background: Aging is associated with increased prevalence of thyroid function abnormalities including hypothyroidism. A meta-analysis showed an increased prevalence and incidence of cardiovascular mortality only in a relatively younger population. Objective: To compare the thyroid function status in IHD patients of different age groups. Methods: This cross sectional study was carried out on 31 IHD subjects aged 35-59 years (Group B1) and 19 IHD subjects aged 60-85 years (Group B2) in the Department of Physiology, Dhaka Medical College, Dhaka from July 2009 to June 2010. For comparison 24 healthy subjects aged 35-59 years (Group A1) and 26 with age 60-85 years (Group A2) were studied. The IHD subjects were selected from coronary care unit of cardiology department and OPD of Dhaka Medical College Hospital, Dhaka. Serum FT3, FT4 and TSH of all subjects were measured by radioimmunoassay. Statistical analysis was done by unpaired Students t test. Results: The mean ± SD of FT3 and FT4 were significantly lower and TSH was significantly higher in Group B1 IHD patients than that of Group A1 healthy subjects, but no difference was found between Group A2 and Group B2 and between Group B1 and Group B2. Conclusion: Thyroid hormone levels are significantly lower in younger IHD population (age 35-59 years) than the age-matched normal controls. DOI: http://dx.doi.org/10.3329/jemc.v2i2.12842 J Enam Med Col 2012; 2(2): 80-84